2014
DOI: 10.1111/ecc.12188
|View full text |Cite
|
Sign up to set email alerts
|

A pathway to empowerment: evaluating a cancer education and support programme in New Zealand

Abstract: Support programmes often benefit cancer patients and their families. This study evaluates how the Living Well Cancer Education Programme (LWCEP), from the Cancer Society of New Zealand, meets the needs of its clients. A purposeful sample of 21 participants representing the normal range of demographic characteristics (age, gender, diagnosis and geographical location) for the programme, participated in semi-structured interviews. Demographic data were subjected to a frequency analysis. Main data were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Thus, the idea that patient satisfaction is a multidimensional concept which includes interaction between patient and caregiver, the presence and competence of the caregiver, the offer and continuity of care, and the characteristics of communication (30) is reinforced. In addition, it is important to emphasize that a patient's self-efficacy is also influenced by their relationship with the health professional through an exchange of information and increased knowledge about treatment, establishing trust and increasing satisfaction (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the idea that patient satisfaction is a multidimensional concept which includes interaction between patient and caregiver, the presence and competence of the caregiver, the offer and continuity of care, and the characteristics of communication (30) is reinforced. In addition, it is important to emphasize that a patient's self-efficacy is also influenced by their relationship with the health professional through an exchange of information and increased knowledge about treatment, establishing trust and increasing satisfaction (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Learning from the experiences of others was a theme described in several papers, and support groups or other networks were important in this context. However, only one study (Kane et al, 2014) described a collective element of patient empowerment within families. Considering the impact of cancer on families, this could be an important area to explore further in relation to facilitators of empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that attending the group was an important way for the participants to obtain information that their HCPs had not provided, and that other participants encouraged and assisted them in looking for further information. Similarly, Kane, Jasperse, Boland, and Herst (2014) described the Living Well Cancer Education Programme (LWCEP) in New Zealand as a source of information and this, combined with the “normalizing effect” of belonging to a cancer community, helped people gain perspective, make increasingly informed choices, gain confidence and communication skills, and feel more in control. Another important point in this particular article was that couples who attended the program together felt that their collective sense of control had been strengthened by their increased communication and problem solving.…”
Section: Thematic Synthesismentioning
confidence: 99%
“…Already existing psycho-pedagogical tools to increase knowledge about the disease show that specific and clear disease information increases patient empowerment and participation. From participation grows knowledge (Alden, 2014; Kane, 2014; Schmidt et al, 2015). There are several studies as well as patient testimonies pointing to the importance of patient participation and self-action in both diagnostic and treatment processes (deBronkart, 2011; McDonald, Bryce, & Graber, 2013).…”
Section: Resultsmentioning
confidence: 99%